2017
DOI: 10.5194/npg-24-61-2017
|View full text |Cite
|
Sign up to set email alerts
|

The fully nonlinear stratified geostrophic adjustment problem

Abstract: Abstract. The study of the adjustment to equilibrium by a stratified fluid in a rotating reference frame is a classical problem in geophysical fluid dynamics. We consider the fully nonlinear, stratified adjustment problem from a numerical point of view. We present results of smoothed dam break simulations based on experiments in the published literature, with a focus on both the wave trains that propagate away from the nascent geostrophic state and the geostrophic state itself. We demonstrate that for Rossby n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…If this balance is disturbed through processes such as the shoaling of isopycnals by strong storms, the flow will adjust itself back to a state of geostrophic balance. This process, known as geostrophic adjustment, was first considered by Rossby in 1938 (19) and has since been investigated in a variety of contexts both linear and nonlinear (20)(21)(22)(23). Common to all those studies is that the flows in question hold less energy at their end states than they do initially, and energy is dispersed in the form of inertial gravity waves (19,24).…”
mentioning
confidence: 99%
“…If this balance is disturbed through processes such as the shoaling of isopycnals by strong storms, the flow will adjust itself back to a state of geostrophic balance. This process, known as geostrophic adjustment, was first considered by Rossby in 1938 (19) and has since been investigated in a variety of contexts both linear and nonlinear (20)(21)(22)(23). Common to all those studies is that the flows in question hold less energy at their end states than they do initially, and energy is dispersed in the form of inertial gravity waves (19,24).…”
mentioning
confidence: 99%
“…The evolution of ISWs are modified by rotation depending on Rossby number, amplitude, and non-dimensional dispersion parameter (e.g., Helfrich and Grimshaw 2008;Coutino and Stastna 2017). In contrast, internal bores on the shelf have large amplitude (isopycnal displacements a 10.1175/JPO-D-21-0095.1.…”
Section: Introductionmentioning
confidence: 99%
“…As described in Coutino and Stastna (2017), without the walls the Poincaré waves steepen and eventually breakdown into a non-linear wave packet as dispersive effects take over. The addition of side walls appears to slow the large-scale breakdown of the leading wave.…”
mentioning
confidence: 98%
“…In the simpler case of a rotating fluid adjusting without the presence of side walls, it has been observed that if dispersive effects are accounted for, a leading solitary wave is created which then breaks down into a nonlinear wave packet as it propagates (Coutino and Stastna (2017)). Additionally, a geostrophic state is created at the site of the initial condition which oscillates at a near inertial frequency and radiates waves.…”
mentioning
confidence: 99%
See 1 more Smart Citation